A case for genomic medicine in South African paediatric patients with neuromuscular disease - Raga, Sharika V.; Wilmshurst, Jo Madeleine; Smuts, Izelle; Meldau, Surita; Bardien, Soraya; Schoonen, Maryke; van der Westhuizen, Francois Hendrikus (Frontiers in Pediatrics, 2022)
Paediatric neuromuscular diseases are under-recognised and under-diagnosed in Africa, especially those of genetic origin. This may be attributable to various factors, inclusive of socioeconomic barriers, high burden of communicable and non-communicable diseases, resource constraints, lack of expertise in specialised fields and paucity of genetic testing facilities and biobanks in the African population, making access to and interpretation of results more challenging. As new treatments become available that are effective for specific sub-phenotypes, it is even more important to confirm a genetic diagnosis for affected children to be eligible for drug trials and potential treatments. This article aims to create awareness of the major neuromuscular diseases clinically diagnosed in South Africa, in the paediatric population. Challenges are highlighted and possible solutions are suggested.